Enhancing shariah-compliant tourism via network of mosque: anasgo - Abdul Latif, Nurfatin Hanani; Mohd Rothi, Nur Amalina; Mohamad Waziril Ghozi, Nasihah; Isnin, Siti Fatimah; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
According to Sir William Muir writes in his book "The Life of Muhammad": "Though crude in material, and insignificant in dimensions, the Mosque of Muhammad is glorious in the history of Islam. Here, the Prophet and his Companions spent most of their time; here, the daily service, with its oft-recurring prayers was first publicly established; and here, the great congregation assembled every Friday, listening with reverence and awe to messages from Heaven. Here, the Prophet planned his victories; here he received embassies from vanquished and contrite tribes; and from hence issued edicts, which struck terror amongst the rebellious to the very outskirts of the peninsula. Hard by, in the apartment of Aisha (one of the wives of the Prophet), he breathed his last, and there, side by side with his first two successors he lies buried." (p.177). Hence, there are many of functionality of a mosque that we can use instead of for prayers purpose and remembering of God (Dhkir) only. Thus, the emerging of Islamic Centre of Network of Mosque that is proposed in this conceptual Business Model, utilizing BMC and VPD will create high values to travelers by providing ideal temporary lodgings and enhancing local homestay business within area of mosque by providing advertisement platform via the proposed AnasGo Platform.